Divine revelation and human practice : response and imaginative inspiration - Clark, Tony, 1961- (James Clarke & Co, 2010)
In this creative contribution to the doctrine of revelation, Clark seeks to develop and articulate an understanding of God's self-disclosure located in the participation of the ecclesiastical community in the trinitarian life of God. Taking Karl Barth's doctrine of the Word of God as his point of departure, and expanding upon the work of Michael Polanyi, Clark demonstrates the integral involvement of human imagination in the revelatory event.